Toll-like Interleukin -1 Receptor Regulator (TILRR) Protein, a Major Modulator of Inflammation, is Expressed in Normal Human and Macaque Tissues and PBMCs - Kashem MA; Li L; Yuan XY; Plummer FA; Luo M (Dove Medical Press, 2022)
Mohammad Abul Kashem,1- 3 Lin Li,2 Xin-Yong Yuan,2 Francis A Plummer1 ,† Ma Luo1,2 1Department of Medical Microbiology and Infectious Diseases, University of Manitoba, Winnipeg, MB, Canada; 2JC Wilt Infectious Diseases Research Center, National Microbiology Laboratory, Public Health Agency of Canada, Winnipeg, MB, Canada; 3Department of Microbiology and Veterinary Public Health, Chittagong Veterinary and Animal Sciences University, Chittagong, Bangladesh†Dr Francis A Plummer passed away on February 04, 2020Correspondence: Ma Luo, JC Wilt Infectious Diseases Research Center, National Microbiology Laboratory, 745 Logan Avenue, Winnipeg, MB, R3E 3L5, Canada, Tel +1 204-789-5072, Fax +1 204-789-2018, Email maluo@phac-aspc.gc.caPurpose: TILRR is a modulator of genes in the NF-κB inflammation pathway. It regulates inflammation-responsive genes, the secretion of inflammatory mediators, and the migration of immune cells. Because inflammation drives the pathogenesis of many infectious and inflammatory diseases, it is important to know the expression of TILRR protein in tissues and cells. This study examined TILRR protein expression in healthy adult human and macaques' tissues and PBMCs (peripheral blood mononuclear cells).Methods and Results: Tissues (trachea, lungs, stomach, small intestine [ileum], cecum, colon, rectum, vagina, cervix, uterus, and penis) and PBMCs from humans and macaques were lysed in RIPA (radioimmunoprecipitation assay) lysis buffer. The TILRR protein was examined by fluorescent Western blot analysis. The relative fluorescence units (rfu) of TILRR protein expression were quantified by Image Studio software (LI-COR). The results showed that adult healthy female (n=1) rectal and cervicovaginal tissues expressed a higher level of TILRR protein than the other tissues (trachea, lungs, stomach, small intestine [ileum], cecum, colon, uterus, and penis) examined. Like humans, the lungs, colon, and rectal tissues of healthy adult female cynomolgus monkeys (Macaca fascicularis) (n=2) expressed the TILRR protein. In addition, PBMCs of healthy adult women (n=4), adult female cynomolgus monkeys (Macaca fascicularis) (n=4), and adult male and female rhesus monkeys (Macaca mulatta) (n=4) showed a similar expression level of TILRR protein (p= 0.2858). TILRR protein was not detected in most of the human cell lines examined, except in Jurkat cells.Conclusion: Our study for the first time showed that TILRR protein is expressed in healthy adult human and monkey tissues and PBMCs. The TILRR protein in these tissues and PBMCs may play a role in the inflammatory response of these tissues and cells in response to infectious pathogens.Keywords: TILRR, tissues, PBMCs, human, rhesus monkey (Macaca mulatta), cynomolgus monkey (Macaca fascicularis), inflammation